USE OF SUPPLEMENTATION OF SYNBIOTIC AND SUMAC Rhus coriaria L. AS PROMETER FOR PRODUCTION OF LAYING HENS - Jasim, Mahdi Salih; Ali, Ruqad Faisal (Diyala Agricultural Sciences Journal, 2017)
This study aimed to evaluate the use of supplementation of synbiotic with different levels of sumac powder as promoter for the production of Lohmman Brown layers. For five months used 216 laying hens at 46 weeks age, distributed in 18 ground pens (1.15 × 2 m pen-1), 12 hens pen-1, and randomly divided in to six treatments (3 Rep. / treat.). The first treatment (T1) were fed a standard diet (control), T2, T3, T4, T5 and T6 were fed a standard diet was supplemented with 0.3% synbiotic, 0.5% sumac, 1% sumac, 0.3% synbiotic + 0.5% sumac powder, and 0.3% synbiotic +1% sumac respectively. The results showed an improvement in the productive performance of birds fed the synbiotic and sumac powder, since significantly increase (P≤0.05) achieved in each of egg production ratio (H.D.%), eggs mass, and feed conversion ratio compared with the control treatment. The effect of supplementation treatments had been enhanced productive performance in birds fed a combination supplementation of synbiotic and sumac compared with birds fed supplementation of synbiotic or sumac alone, means that got a synergistic effect between the synbiotic and sumac. The improvement in the productive performance and quality of eggs produced that reflection of the improvement in each the microbial balance of the intestines, histological characteristics of the intestines and immune response, were significantly decreased both of the numbers of total bacteria, and Coliform, and increased significantly the number of the lactic acid bacteria, also significantly increased the length of villi, depth of the crypts, and titer of antibodies against Newcastle disease in birds fed synbiotic and sumac, compared with the birds of the control treatment.